Collaborative Governance dalam Pengembangan Pariwisata di Kabupaten Pacitan - Buffon Yoppy Trie Ambodo; Anggraeny Puspaningtyas; Supri Hartono (Perspektif Administrasi Publik dan hukum, 2026)
One of the key strategic sectors that contributes significantly to driving economic growth, improving community welfare, and strengthening regional development is tourism. Pacitan Regency possesses significant potential in natural tourism, cultural tourism, and the creative economy; however, its development still faces various challenges, including limited infrastructure, accessibility issues, and coordination among stakeholders. The application of collaborative governance in Pacitan Regency's tourist growth is the main subject of this study, which also looks at the enabling and impeding variables. A descriptive qualitative approach is used in the study. Data were obtained through interviews, observations, documentation, and document studies, and were subsequently analyzed by applying the Miles and Huberman interavtive model. Ansell and Gash's Collaborative Governance model, which incorporates initial contextual factors, facilitative leadership, institutional design, and the collaborative process, served as the foundation for the analysis. The findings suugest that collaborative governance in tourism development in Pacitan Regency has been implemented relatively well. The Department of Tourism, Culture, Youth, and Sports plays an active role as a facilitator of collaboration, supported by clear regulations, regular coordination forums, and the involvement of government agencies, tourism awareness groups (Pokdarwis), business actors, the media, and local communities. The main supporting factors are the region’s substantial tourism potential and the established cooperation among stakeholders, while the inhibiting factors include differences in perspectives among actors and limitations in infrastructure. This study implies the importance of strengthening stakeholder synergy, enhancing community capacity, and improving infrastructure development to achieve sustainable tourism development in Pacitan Regency.